2000
DOI: 10.1136/bmj.321.7267.994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a programme of multifactorial home visits on falls and mobility impairments in elderly people at risk: randomised controlled trial

Abstract: Objective To evaluate whether a programme of multifactorial home visits reduces falls and impairments in mobility in elderly people living in the community. Design Randomised controlled trial with 18 months of follow up. Setting Six general practices in Hoensbroek, the Netherlands. Participants 316 people aged 70 and over living in the community, with moderate impairments in mobility or a history of recent falls. Intervention Five home visits by a community nurse over a period of one year. Visits consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0
10

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(171 citation statements)
references
References 16 publications
4
157
0
10
Order By: Relevance
“…Whereas these measures may decrease the risk of falling, the magnitude of the effect and their effect on hip fracture risk have been disappointing. 21,22 Another approach is to decrease the impact of falling with the use of hip protectors. Controlled trials suggest that hip protectors confer considerable protection against hip fracture risk, but compliance is a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas these measures may decrease the risk of falling, the magnitude of the effect and their effect on hip fracture risk have been disappointing. 21,22 Another approach is to decrease the impact of falling with the use of hip protectors. Controlled trials suggest that hip protectors confer considerable protection against hip fracture risk, but compliance is a problem.…”
Section: Discussionmentioning
confidence: 99%
“…The data are drawn from the baseline phase of a randomized controlled trial, which was conducted from September 1997 to June 1999 (Van Haastregt et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…(8) In the community, targeted or untargeted education about falls or fear of falling with no follow-up of recommendations has no evidence of effectiveness [61,80,89,91,92,95].…”
Section: Evidence From Risk Factor Studiesmentioning
confidence: 99%
“…Our extended search identified ten more studies [80][81][82][83][84][85][86][87][88][89]. Three additional studies [90][91][92] which met our criteria were identified by Feder et al [7] and six [90,91,[93][94][95][96] by the AGS panel [8].…”
Section: Evidence From Intervention Effectiveness Studiesmentioning
confidence: 99%